Vim line technique thalamotomy for Parkinson tremor: Case series. (2020) - Fahmi, Achmad; Subianto, Heri; Nugraha, Priya; Hamdan, Muhammad; Al Fauzi, Asra; Sensusiati, Anggraini Dwi; Utomo, Budi; Sarno, Riyanarto; Turchan, Agus; Macfoed, Mohammad Hasan; Taira, Takaomi; Bajamal, Abdul Hafid
Highlights: Vim thalamotomy is a usual procedure to control Parkinson tremor. The ventral intermediate nucleus of the thalamus is difficult to identify. The precision is crucial importance for the successful Vim thalamotomy. Vim line technique (VLT) is useful for the determination of the vim location. Abstract: Introduction: The ventral intermediate (Vim) nucleus of the thalamus is difficult to identify even with 3 T magnetic resonance imaging. Stereotactic Vim thalamotomy is a usual procedure to control Parkinson tremor. Successful relieving of the tremor depends on the accuracy of defining the Vim location. Presentation of cases: Three patients with Parkinson tremor were subjected to stereotactic thalamotomy using the Vim line technique (VLT) so as to precisely determine the Vim location. All patients showed good results, with improved tremors, as indicated by the UPDRS score, without any complications. Discussion: The precise targeting of the Vim nucleus is crucial importance for the successful Vim thalamotomy. Various method has been developed to determine Vim location. Atlas based and Guiot's technique routinely used by neurosurgeon. VLT is a new technique that has been developed to determine the Vim location on MRI. Conclusion: VLT is useful for the determination of the Vim location. However, further research is warranted to prove its effectiveness.